Beach Tourism Attractions in Nellore District - Divya Prakash Ojha (International Journal of Land, 2024)
Nellore district, situated along the picturesque southeastern coast of Andhra Pradesh, India, is celebrated for its serene and captivating beaches that draw tourists in search of peace, relaxation, and natural splendor. The district's extensive coastline presents a harmonious blend of rich cultural heritage, unique biodiversity, and abundant leisure opportunities, making it a promising destination for beach tourism. This study delves into the prominent beach tourism attractions in Nellore, their historical and cultural significance, the challenges they face, and the prospects for their sustainable development. An extensive review of literature underscores the vast untapped potential of the region, revealing how strategic interventions can transform it into a vibrant tourism hub. However, the study also identifies pressing challenges, including inadequate infrastructure, environmental concerns, and a lack of cohesive tourism policies. To address these issues, the study proposes several recommendations focused on enhancing infrastructure, promoting eco-tourism practices, and fostering active community involvement to ensure long-term benefits. By emphasizing sustainable tourism development, this analysis aims to highlight the role of responsible planning in unlocking Nellore’s full potential as a premier beach tourism destination.
Keywords: Andhra Pradesh; Biodiversity; Eco-Tourism; Mypadu Beach; Nellore district; Ramayapatnam Beach; beach tourism; coastal attractions; cultural heritage; sustainable tourism